Pengaruh Kepemilikan Manajerial, Modal intelektual, Struktur Modal Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Yuli Angraini; Fasridon Fasridon (Universitas Sains dan Teknologi Komputer, 2021)
This study aims to determine the effect of managerial ownership, intellectual capital, capital structure on firm value with profitability as an intervening variable. The population used in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) 2018-2022. The sampling technique used is purposive sampling and data management using SPSS 16. This type of research is a research with a quantitative approach. The analytical method used is multiple regression analysis. The research results obtained based on the partial test (t test) obtained: (a) Managerial Ownership does not partially have a significant effect on Profitability (b) Intellectual Capital partially has a significant effect on Profitability (c) Capital Structure partially has a significant effect on Profitability. (d) Managerial Ownership partially has a significant effect on Firm Value, (e) Intellectual Capital partially does not have a significant effect on Firm Value (f) Capital Structure partially has a significant effect on Firm Value. (g) While for the results of intervening variables using path analysis test shows that managerial ownership and capital structure have a significant effect on firm value through profitability but intellectual capital cannot significantly affect firm value through profitability.